PENERAPAN INOVASI TEKNOLOGI DAN PENDAPATAN USAHATANI PADI - Yanter Hutapea; Tumarlan Thamrin; Yanto Pandu (Publikasi Penelitian Terapan dan Kebijakan, 2020)
The aim of this assessment was to know the application of technology which was done by participant farmer and non participant farmer of Prima Tani, production and rice farming income, and also the relationship between the application of technology with rice farming income. Data of rice farming activity in wet season 2006/2007 was collected in August until September 2007 by interviewing participant farmer of Prima Tani in Kertosari Village and non participant farmer as a comparison in Purwakarya Village, Purwodadi Sub-district, Musi Rawas Regency. Sample (owner of the foundation) was taken by Disproportionate Stratified Random Sampling. The result of this assessment showed that the score of technology application of participant and non participant farmer with magnitude of 16,38 and 14,37, respectively, but statistically the difference was insignificant and including on medium category of technology application. The farming productivity of participant farmer was 7.118 kg harvesting dry grain/ha and 7.215 kg harvesting dry grain/ha of non participant farmer. Rice farming total cost of participant and non participant farmer with magnitude of Rp 5.786.035/ha and Rp 6.663.875/ha respectively. Rice farming income of participant farmer was higher than non participant farmer with magnitude of Rp 8.228.915/ha and Rp 7.235.435/ha, respectively. Statistically, the relationship between applicated technology with rice farming income was insignificant. It is suggested to intensify agricultulcure extension about technological innovation in other to impact on increasing production, farming income and efficiency of production factors.